Analyzing some of the Biokinematic Variables for one of Nineveh Champions in 110m Hurdles - Ghanem, Thaer (Journal of Physical Education, 2010)
The study is mainly dealing with the large developments of the athletic stadiums, the kinetic performance of 110m hurdles and the role of mechanical analysis in this aspect. The study aims at identifying the values of some biokinematic variables for one of Nineveh champions in 110m hurdles.Descriptive approach with survey is used for it is suitable with the study and the study sample consists of one runner (one of Nineveh champions in 110m hurdles. Data were collected through video recording and some of computer software were used in analysis including Excel, AutoCAD 2009, Premear, I filma. The study, based on the results obtained, concludes the following:• The study sample have not achieved the good values for some of the biokinematic variables examined. • The weak skill performance for the study sample has indirectly affected the digital performance level.